Gender, sex, and sexuality among contemporary youth - Claster, Patricia Neff; Blair, Sampson Lee (Bingley, U.K. : Emerald Publishing Limited, 2017)
Researchers, practitioners, and parents have increasingly become concerned about issues related to sex, gender, and sexuality among children and adolescents. With access to the Internet, young people around the globe can readily obtain virtually any and all information they seek concerning sex and sexuality. In many cultures, the clothing and fashions of children, adolescents, and young adults are increasingly merging, leaving little clear distinction between them, and creating what some consider to be the'sexualization' of children's and adolescents' clothing. Coinciding with such changes, young people are more openly expressing their own gender identity, often leading to considerable social debate about feminine and masculine identities, and also transgendered identities. This collection provides unique insight into identity formation for contemporary youth and examines the evolving norms concerning sex, gender, and sexuality in the lives of children and adolescents addressing topics including the development of gender identity, sexual behavior among youth, LGBT youth, transgendered youth, parental and peer influences upon the development of gender and gender identity and dating violence.
Prelims --'Dare to be Different' : how religious groups frame and enact appropriate sexuality and gender norms among young adults -- Estimating the status and needs of homeless LGBT adolescents: advocacy, identity, and the dialectics of support -- The intersex kids are all right? Diagnosis disclosure and the experiences of intersex youth -- Examining the family transition: how parents of gender-diverse youth develop trans-affirming attitudes -- Let's talk about sex for money: an exploration of economically motivated relationships among young, black women in Canada -- Educational attainment and sexual orientation in adolescent and young adult males --'To Feel Him Love Me': emerging intersections of identity, queerness, and differing ability -- Sexual debut education: cultivating a healthy approach to young people's sexual experiences -- Breaking up is hard to do: teen dating violence victims' responses to partner suicidal ideation -- Two by two: heteronormativity and the Noah story for children -- About the editors -- Index.
Includes index.
Includes bibliographical references.
Keywords: Gender identity; Children -- Sexual behavior; Teenagers -- Sexual behavior